Large-scale single-nuclei profiling identifies role for ATRNL1 in atrial fibrillation - Matthew C. Hill; Bridget Simonson; Carolina Roselli; Ling Xiao; Caroline N. Herndon; Mark Chaffin; Helene Mantineo; Ondine Atwa; Harshit Bhasin; Yasmine Guedira; Kenneth C. Bedi; Kenneth B. Margulies; et al. (Nature Communications)
Abstract Atrial fibrillation (AF) is the most common sustained arrhythmia in humans, yet the molecular basis of AF remains incompletely understood. To determine the cell type-specific transcriptional changes underlying AF, we perform single-nucleus RNA-seq (snRNA-seq) on left atrial (LA) samples from patients with AF and controls. From more than 175,000 nuclei we find that only cardiomyocytes (CMs) and macrophages (MΦs) have a significant number of differentially expressed genes in patients with AF. Attractin Like 1 (ATRNL1) was overexpressed in CMs among patients with AF and localized to the intercalated disks. Further, in both knockdown and overexpression experiments we identify a potent role for ATRNL1 in cell stress response, and in the modulation of the cardiac action potential. Finally, we detect an unexpected expression pattern for a leading AF candidate gene, KCNN3. In sum, we uncover a role for ATRNL1 which may serve as potential therapeutic target for this common arrhythmia.